Movement analysis in dance therapy: Semantics of movement qualities, rhythm and shape according to Laban and Kestenberg - Koch, Sabine C (Acta Universitatis Carolinae. Kinanthropologica, 2011)
This paper outlines how approaches from dance therapy can contribute to our understand- ing of movement. Two major systems of movement analysis (notation and observation) are introduced focusing on movement qualities, for which they provide basic categories and a basic vocabulary. It is argued that these approaches can contribute to a fuller understand- ing of movement and its semantics, particularly in its qualitative and dynamic aspects.
Keywords: Humans; Movement; metafora; kvality pohybu; taneční/pohybová terapie; pohyb; Metaphor; Exercise Therapy; uvědomování si; Dancing; terapie cvičením; lidé; tanec; pohybový rytmus; Awareness